Application of Tin(II) Chloride Catalyst for High FFA Jatropha Oil Esterification in Continuous Reactive Distillation Column - Ratna Dewi Kusumaningtyas; Imam Novrizal Aji; Hadiyanto Hadiyanto; Arief Budiman (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
The application of heterogeneous solid acid catalysts in biodiesel production has become popular and gained significant attention over the last few years. It is since these types of catalysts hold the benefits in terms of easy separation from the product, reusability of the catalyst, high selectivity of the reaction. They are also considered sustainable and powerful particularly in organic synthesis. This work studied the use of tin(II) chloride as solid Lewis acid catalyst to promote the esterification reaction of high Free Fatty Acid (FFA) jatropha oil in continuous reactive distillation column. To obtain the optimum condition, the influences of reaction time, molar ratio of the reactant, and catalyst were investigated. It was revealed that the optimum condition was achieved at the molar ratio of methanol to FFA at 1:60, catalyst concentration of 5%, and reaction temperature of 60°C with the reaction conversion of 90%. This result was significantly superior to the identical reaction performed using batch reactor. The esterification of high FFA jatropha oil using reactive distillation in the presence of tin(II) chloride provided higher conversion than that of Amberlyst-15 heterogeneous catalyst and was comparable to that of homogenous sulfuric acid catalyst, which showed 30 and 94.71% conversion, respectively. The esterification reaction of high FFA jatropha oil was subsequently followed by transesterification reaction for the completion of the biodiesel production. Transesterification was carried out at 60 °C, molar ratio of methanol to oil of 1:6, NaOH catalyst of 1%, and reaction time of one hour. The jatropha biodiesel product resulted from this two steps process could satisfy the ASTM and Indonesian biodiesel standard in terms of ester content (97.79 %), density, and viscosity.